Trends and Predictors of Venous Thromboembolism and Major Hemorrhagic Events in Hospitalized Leukemia Patients: A Cross-Sectional Analysis of the NIS (2016–2020) - Daniel Antwi-Amoabeng; Bryce D. Beutler; Vijay Neelam; Mark Ulanja (Clinics and Practice)
Background/Objectives: Venous thromboembolism (VTE) and major hemorrhagic events are significant complications in hospitalized leukemia patients, but contemporary analyses of their epidemiology, predictors, and impact on clinical outcomes remain limited. Methods: We conducted a cross-sectional study using the National Inpatient Sample (NIS) database from 2016 to 2020. Hospitalized leukemia patients were identified using ICD-10 codes. Trends in the incidence of venous thromboembolism (VTE) and bleeding were assessed across the years, and multivariable logistic regression models were used to evaluate the predictors of VTE and bleeding. We assessed the influence thromboembolic and hemorrhagic complications on length of stay, cost, and mortality outcomes. Results: Among 430,780 leukemia hospitalizations, the overall incidence of VTE was 5.4% and remained stable throughout the study period (p = 0.09), while hemorrhagic events = 5.6%) showed a significant upward trend (p = 0.01). Cerebrovascular accidents, central venous catheter insertion, and protein calorie malnutrition (PCM) were significant predictors of both VTE and hemorrhage. PCM demonstrated a dose-dependent relationship with both complications. VTE was associated with a 33.5% increase in length of stay (LOS) and a 35% increase in cost of care (COC). Hemorrhage was associated with 23.2% increase in LOS and 32.6% increase in COC. Only hemorrhagic events were independently associated with increased mortality (adjusted OR 2.88, p < 0.001). Conclusions: The incidence of VTE in hospitalized leukemia patients has remained stable while hemorrhagic complications have increased significantly. Nutritional status represents a potentially modifiable risk factor for both VTE and bleeding complications. The competing risk between thrombosis and hemorrhage varies with age and nutritional status, suggesting the need for nuanced thromboprophylaxis strategies in this vulnerable population.